Freud : moments of modernism - Long-Innes, Francis (Department of English Language and Literature, 2016)
The word "moment" - from the Latin movere (to move) - can be understood in various senses. It is a point of time, an instant; it connotes importance, or weight; in 1666, according to the OED, it could be used to suggest a "definite stage or turning point in a course of events"; in 1691 it came to mean a "cause or motive of action, a determining influence or consideration" ... This dissertation stems from the conviction that the importance and weight of Sigmund Freud's "discovery" and elaboration of psychoanalysis - its impact as a turning point for western modes of intellectual activity, and as a determining consideration for western culture as a whole - has been so profound that it would be impossible to seek from within it the precise measure of its influence. Across modern philosophy, the human sciences, and the arts - from surrealism to pop art, from advertising to social welfare policies - Freud's psychoanalysis permeates the ways in which we live, and is one of the key elements of that experience of modernity we can loosely call "modernism". The dissertation locates a number of moments ·of modernism in and around Freud's work - with attention to Freud's relation to the reading and interpretive practices of the twentieth century: Chapter One examines some of the ways in which psychoanalysis and literary studies have met, intersected and, at times, bypassed one another over the past few decades, in a flurry of encounters which have yet to settle into any definitive shape. Chapter Two responds to Stanley Fish's recent attack on Freud's scientific integrity in the "Wolf-man". The chapter focuses, in other words, on one particular strand of the critical tradition defined in the second section of Chapter One. Chapter Three - which concerns the famous case of "Dora" - attempts, first, to restore some sense of the theoretical moment in Freud's work represented by the case, and second, to re-introduce the question of history into what has become the critics' story of Freud's failure to get to the bottom of Dora's hysteria. The aim of this chapter is to suggest a way beyond the contradiction in which Freud is persistently invoked, in feminist criticism, as both liberator and oppressor, hero and villain. Chapter Four turns back to the interface between psychoanalysis and literature. Its focal point is a different permutation from that manifested in the "Dora" case history of Freud's life-long quest to solve the "riddle" of femininity. The chapter examines some of the problems Defoe's novel Moll Flanders has posed to a tradition of patriarchal literary criticism. These problems, it argues, are inseparable from questions of representation, female identity and the notion of ''femininity" itself - the same questions which proved so intrusive in Freud's narrative of the case of Dora. This dissertation is concerned not only with the apparent "logic" of the arguments it confronts, but also with the· deeper constitution of that logic in and through the complex textures of writing. It aims to demonstrate that one of the most powerful moments of modernism in Freud's work lies in the stimulus it provides to an art of interpretation constantly attentive to the complexity of these textures.